2005
DOI: 10.1186/1471-2296-6-50
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of disseminated cutaneous zoster in an immunocompetent patient

Abstract: Background: Disseminated cutaneous herpes zoster in healthy persons is uncommon, though it has been described in immunocompromised patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…Malignancy, HIV infection, therapy with immunosuppressive medications and diabetes all increase risk 19. Though DCHZ has been reported in immunocompetent individuals, it is rare 20. Two recent reviews identified only 30 cases of DCHZ in immunocompetent patients, the majority of whom were 65 years of age or older 21 22…”
Section: Discussionmentioning
confidence: 99%
“…Malignancy, HIV infection, therapy with immunosuppressive medications and diabetes all increase risk 19. Though DCHZ has been reported in immunocompetent individuals, it is rare 20. Two recent reviews identified only 30 cases of DCHZ in immunocompetent patients, the majority of whom were 65 years of age or older 21 22…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate of disseminated herpes zoster infections is very high, at 10-40% in patients with decreased immunity, especially in patients with HIV infections, hematological malignancies, and those who are undergoing chemotherapy, since they have a decreased number and decreased activity of T lymphocytes. The recurrence rate is also high, so 10 mg/kg (or 500 mg/m 2 ) of acyclovir is IV administered every 8 hours and replaced with oral agents (valacyclovir, famciclovir) when symptoms are controlled, or patients with less severe immune suppression can be administered with oral agents from the beginning [2-6]. …”
Section: Discussionmentioning
confidence: 99%
“…Disseminated herpes zoster is defined as more than 20 small widespread vesicles resembling varicella outside the area of the primary and adjacent dermatomes, and may or may not involve visceral organs. It has been mainly described in the elderly or persons with immunosuppression due to HIV infection, hematologic malignancy, or chemotherapy; in otherwise healthy individuals it is very rarely reported 5,8,9 . Therefore, a patient with disseminated herpes zoster, with no known co-factors (as noted above) deserves a complete work-up to elucidate any underlying malignancy or immunodeficiency 3,4,10,11 .…”
Section: Discussionmentioning
confidence: 99%